Evaluating the Acceptance of Project Management Platforms in Distributed Software Teams: An Experience Report - Lopes, Andressa dos Santos; Sobrinho, Marialina Corrêa; Santos, Clayton Andre Maia dos; Silva, Deivid Eive dos S. (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de SoftwareDO - 10.5753/sbqs.2025.15055, 2025)
Geographically distributed software development teams often face challenges in adopting project management tools, with decisions frequently based on comparisons that overlook human and contextual factors. This study investigates the acceptance of GitHub Projects, Huly, and ClickUp within a Brazilian software development organization with distributed collaborators. Specialists from the Software Engineering team participated, representing various organizational roles and product lines. Data were collected through a structured questionnaire, based on indicators from the Technology Acceptance Model (TAM3), and semi-structured interviews. Quantitative and qualitative analyses revealed that ClickUp had the highest acceptance rates, particularly regarding perceived ease of use and perceived usefulness. The results also highlighted that information centralization, platform stability, and feature completeness are critical factors for tool adoption. This research contributes to the field of Software Quality by offering empirical evidence to support decision-making during tool transitions.